Determinant aspects of the deciduous fruit production in the province of Tungurahua, Ecuador - Viera, William; Instituto Nacional de Investigaciones Agropecuarias (INIAP), Av. Eloy Alfaro N30-350 y Av. Amazonas, Quito. (2020)
The province of Tungurahua is well known for the production of deciduous fruit trees in Ecuador, however, its production is impacted by some issues that affect productivity. The purpose of this investigation was to conduct a diagnosis of the production system of deciduous fruit trees in 6 locations in Tungurahua province. Surveys were carried out to obtain information on 117 production units (farms). A regression model was used to determine the relationship between the variables and their incidence in the production system. The results showed that peach (Prunus persica) is the fruit crop with highest yield (16.19 t ha-1), followed by apple (Malus domestica) (13.36 t ha-1) and pear (Pyrus communis) (13.15 t ha-1). Apple cultivars Emilia and Golden Delicious, cv. Uvilla of pear and Conservero Amarillo of peach were the most cultivated in Tungurahua. The main factors that influenced the farmer income were: Land area used for cultivation, reason for growing fruit trees, age of the producer, fruit selection and type of production. It is necessary to advocate to expand the cultivated land area of these fruit crops in order to satisfy local demand and compete with imports of these fruits.